Validity of total polar compound and its three components in monitoring the evolution of epoxy fatty acids in frying oil: Fast food restaurant conditions. (30th March 2023) - Li, Xu; Xing, Changming; Wang, Zhisheng; Chen, Zike; Sun, Wenxing; Xie, Dan; Xu, Guangfei; Wang, Xingguo
Highlights: Epoxy fatty acids in fried oil under fast food restaurant conditions were studied. More epoxy fatty acids were generated in edible oil with high oleic acid content. Epoxy fatty acids can be predicted by TPC with the exponential equation. Epoxy fatty acids in fried high oleic sunflower oil were lower than 7 mg/g. Risk of epoxy fatty acids can be well monitored by current TPC index. Abstract: This study evaluated the validity of total polar compounds (TPC) and its three components in monitoring the evolution of epoxy fatty acids in frying oil under fast food restaurant conditions. The content of epoxy fatty acids can be predicted using the TPC rather than oxidized triglyceride monomer. When TPC content reached 24 g/100 g, 25 g/100 g, and 27 g/100 g, the epoxy fatty acid content in oil was found to be 1.47–3.63 mg/g, 1.58–4.06 mg/g, and 1.83–5.08 mg/g, respectively. More epoxy fatty acids were generated in high oleic sunflower oil than in canola and cottonseed oil during frying. At current discarding points of TPC 24–27 g/100 g, its epoxy fatty acid content was 3.63–5.08 mg/g, which was lower than the limit of 7 mg/g recommended by Max Rubner-Institut in Germany. Our results indicate that the risk of epoxy fatty acids can be monitored using the current TPC index.